Safety of home-based cardiac rehabilitation: A systematic review - Stefanakis, Marios; Batalik, Ladislav; Antoniou, Varsamo; Pepera, Garyfallia (Heart & lung, 2022)
BACKGROUND: Cardiac rehabilitation is an evidence-based intervention that aims to improve health outcomes in cardiovascular disease patients, but it is largely underutilized. One strategy for improving utilization is home-based cardiac rehabilitation (HBCR). Previous research has shown that HBCR programs are feasible and effective. However, there is a lack of evidence on safety issues in different cardiac populations. This systematic review aimed to provide an evidence-based overview of the safety of HBCR. OBJECTIVES: To examine the incidence and severity of adverse events of HBCR. METHODS: The following databases were searched: CINAHL, The Cochrane Library, Embase, MEDLINE, PubMed, Web of Science, Global Health, and Chinese BioMedical Literature Database for randomized controlled trials. The included trials were written in English and analyzed the incidence of adverse events (AEs) as a primary or secondary intervention outcome. RESULTS: Five studies showed AEs incidence, of which only one study reported severe AE associated with HBCR exercise. The incidence rate of severe AEs from the sample (n = 808) was estimated as 1 per 23,823 patient-hour of HBCR exercise. More than half patients included were stratified into a high-risk group. In the studies were found no deaths or hospitalizations related to HBCR exercise. CONCLUSION: The risk of AEs during HBCR seems very low. Our results concerning the safety of HBCR should induce cardiac patients to be more active in their environment and practice physical exercise regularly.
Keywords: Exercise Therapy; Cardiac events; Cardiovascular Diseases; Safety; Exercise; Humans; kardiovaskulární rehabilitace; Cardiac Rehabilitation; Adverse events; terapie cvičením; kardiovaskulární nemoci; lidé; cvičení; Home-based cardiac rehabilitation; Telerehabilitation